ANALYSIS OF LIQUID CREATION PROCESS IN SUGAR FACTORY EVAPORATOR STATION - Hidayat, Fadly Rohyan Hidayat; Jannati, Eidelweis Dewi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Sugar production in the country is increasingly unable to meet consumption needs, so sugar imports since the beginning of 1990 continue to increase from year to year. PG Jatitujuh is one of the activity units under the management of PT. RNI (Rajawali Nusantara Indonesia). PG Jatitujuh has a production capacity of ± 4000 TCD and has a land status of HGU is quite extensive, so that where sugar mills with the application of cultivation and milling management patterns in the same management is very potential in improving its efficiency. Evaporation is a process that aims to attach a solution consisting of volatile solvents and non-volatile solutes (Widjaja, 2010). So evaporation is the process of attachment or thickening of liquid solution by eliminating or reducing the moisture content so that a concentrated liquid solution obtained a higher concentration (Fadly, 2021). The research method conducted directly by interviewing field supervisors, foreman and workers at the sugar factory evaporation station, data analysis obtained by measuring the variable evaporation process at the station includes temperature, pressure, and evaporation process.